Vietnam : Maximizing Finance for Development in the Energy Sector - World Bank Group (World Bank, Washington, DC, 2019)
Vietnam has successfully developed the electricity and gas sectors that have contributed substantially to the economic development of Vietnam. To date, near universal electrification has been achieved, and the industrial, commercial, and residential sectors benefit from increasingly reliable electricity and gas supply. By early 2018, 99.9 percent of the country's communes and 99 percent of its rural households were connected to the grid. Both EVN and PVN, the state-owned electricity and gas utilities, are operationally and technically strong. Vietnam has a hydropower system, claiming 38 percent of installed capacity in 2017, followed by coal (34 percent) and natural gas (18 percent). Future investment requirements in generation are huge, and the country is expected to increase generation capacity from the current 42 GW to 100 GW by 2030. Because mostdomestic hydropower resources have already been developed, and to reduce the planned scale-up of coal-fired power generation, Vietnam has established renewables targets for solar and wind (18 GW by 2030). Starting in 1995, PVN, jointly with international oil and gas companies, developed large-scale gas fields in offshore central and southern Vietnam. In 2017, total offshore gas production was about 10 bcm, mostly destined for gas-to-power. PVN is one of the most significant enterprises operating in the Vietnamese economy, accounting for about 20 percent of national GDP and contributing to 20–30 percent of state budget revenues. To improve the efficiency of the gas and power sector, the government has embarked on introducing competition in those sectors. Electricity liberalization started in 2004 with the unbundling of EVN, the establishment of a regulator, and the introduction of a competitive generation market to ensure long-term sustainability of the power supply. The wholesale electricity market will be fully operational by 2021, allowing large eligible consumers to contract directly with power generators. The government is embarking on a similar liberalization process for gas, is currently preparing a relevant restructuring roadmap for PVN, and introducing a legal and regulatory framework for promoting LNG development, especially for gas-to-power.